Several different cytogenetic clones arising during treatment of Philadelphia positive chronic myeloid leukemia with tyrosine kinase inhibitors lead to the progression into Philadelphia negative acute myeloid leukemia - Denčić-Fekete, Marija; Leković, Danijela; Djordjević, Vesna; Jovanović, Jelica; Todorić-Živanović, Biljana; Jaković, Ljubomir; Bogdanović, Andrija (Vojnosanitetski pregled, 2021)
Introduction. Additional karyotype abnormalities in the Philadelphia-positive (Ph+) clone can emerge during the progression of chronic myeloid leukemia (CML) and are often associated with the resistance to treatment with tyrosine kinase inhibitors (TKI). Sometimes, during the TKI treatment, karyotype abnormalities can appear in the Philadelphia-negative (Ph-) cells as well but do not seem to adversely affect the outcome except for chromosome 7 abnormalities. Case report. The patient presented was in the chronic phase of Ph+ CML with highly diverse karyotype abnormalities. The abnormalities appeared in three unrelated clones during the TKIs treatment, followed by the evolution of the disease into acute myeloid leukemia (AML). The primary Ph+ clone was revealed during the chronic phase of CML, and therapy with imatinib mesylate was commenced. After a three-year hematologic and cytogenetic remission period, the evolution of the primary clone was noticed. Nilotinib was introduced, leading to a good molecular response and the disappearance/loss of the Ph+ clone with additional abnormalities but with the appearance of the Ph- clone with trisomy 8. Finally, after 5.5 years of nilotinib therapy, the Ph- clone with monosomy 7 occurred during the deep molecular response for BCR-ABL. At that time, the FISH analysis for trisomy 8 was negative, but the rise in blast count was noticed in the bone marrow, and the diagnosis of the secondary AML was established soon after. Conclusion. The achievement of the deep molecular response in CML patients does not rule out regular cytogenetic testing of their bone marrow. This is of crucial importance for detecting adverse karyotype abnormalities leading to the development of the myelodysplastic syndrome and AML.
Keywords: leukemia, myelogenous, chronic, bcr-abl positive; leukemia, myeloid, acute; karyotyping; enzyme inhibitors; cytogenetics